Class Consciousness and Socio-Economical Conflict: A Cogitation of Katherine Mansfield’s “The Doll’s House” - et. al., Dr Ajay Prakash Pasupulla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
“Class Consciousness and Socio-Economical Conflict: A Cognition of Katherine Mansfield’s “The Doll’s House”” is an attempt to explore class consciousness and socio-economical conflict and prejudice insinuated in Mansfield’s short story, “The Doll’s Hose”. Mansfield lived between 14th October 1888 and 9th January 1923 in New Zealand and is New Zealand’s famous writer. The present research paper investigates the notion of class conflict and class prejudice seen Mansfield’s society through the socio-economic status of the Kelveys and Burnells. The Kelveys are portrayed as underprivileged and the Burnells are depicted as socially and economically affluent. The social hierarchal structure dealt in the story renders a space to trace the conflicts existing between the classes. The present paper traces the distinct lines that is draw between these two classes. It analyses what made the young minds to prioritize class discrimination and what is the cause behind it. Besides, it ventures to discover the position of grownups in class discrimination and class conflict and their contribution to such social evils.